2020
DOI: 10.4314/rjmhs.v3i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Jaundice Risk Factors at a District Hospital in Rwanda

Abstract: Background Neonatal jaundice is one of the most common reasons for hospital admission in the neonatal unit, and it is associated with significant morbidity and mortality. Objective To assess risk factors associated with neonatal jaundice among newborns at a District Hospital in Rwanda.  Methods A quantitative approach has been used with a retrospective cross-sectional design. Two hundred and ten files were used as sample size. Stratified proportional sampling was used for the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
3
7
1
Order By: Relevance
“…However, it absolutely was beyond a nding from Pakistan (27.6%) [11], Benin (26.5%) [21] and Ghana (32.9%) [32]. It was also quite higher as compared to nding from Nepal [18], Indonesia (4.08%) [33], Iran (12.6%) [34], Congo (7.2%) [35], Uganda (22.7%) [36] and Saint Paul's millennium medical college of Ethiopia (13.3%) [27].This nding was concordant with a previous study conducted in Iran (44.8%) [37], Southeast Nigeria (35%) [38], Rwanda (44.3%) [22], and Black lion Ethiopia [39]. This disparity could be due to sampling size, study period difference, study design, study area, methodology difference, and coverage of obstetrics care, de nitions of hyperbilirubinemia, and characteristics of the study participant.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, it absolutely was beyond a nding from Pakistan (27.6%) [11], Benin (26.5%) [21] and Ghana (32.9%) [32]. It was also quite higher as compared to nding from Nepal [18], Indonesia (4.08%) [33], Iran (12.6%) [34], Congo (7.2%) [35], Uganda (22.7%) [36] and Saint Paul's millennium medical college of Ethiopia (13.3%) [27].This nding was concordant with a previous study conducted in Iran (44.8%) [37], Southeast Nigeria (35%) [38], Rwanda (44.3%) [22], and Black lion Ethiopia [39]. This disparity could be due to sampling size, study period difference, study design, study area, methodology difference, and coverage of obstetrics care, de nitions of hyperbilirubinemia, and characteristics of the study participant.…”
Section: Discussionsupporting
confidence: 87%
“…There is a multiplicity of risk factors associated with maternal, prenatal, and neonatal factors related to the occurrence of neonatal hyperbilirubinemia that can be modi able and manageable [14][15][16][17][18][19][20][21]. In Nigeria, neonatal sepsis, prematurity, and G-6PD de ciency are factors signi cantly associated with neonatal hyperbilirubinemia [21] while in Rwanda, birth weight, gestational age, neonatal gender, method of delivery, blood group incompatibility, infections, cesarean section, and prematurity are signi cantly associated with neonatal hyperbilirubinemia [22].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the CD accounts for 48.60 and 56.52% of Xiangxi and NICU newborns, which were higher than the Chinese average in 2018 (36.7%) (33,35). The characteristics of pregnancy and newborn in advanced maternal age (36), high CD rates (37), and premature infants (28,29) increased the prevalence of jaundice. In conclusion, pregnancy characteristics were associated with the occurrence of newborn diseases, which required more attention and in-depth exploration.…”
Section: Discussionmentioning
confidence: 59%
“…Two cross-sectional studies from Iran considered the age extremes, less than 18 and more than 35 years, as a risk factor [17,18]. Moreover, Murekatete et al reported that the majority of mothers with infants diagnosed with neonatal indirect hyperbilirubinemia were aged between 25 years and 35 years in Rwanda District Hospital [19].…”
Section: International Journal Of Pediatricsmentioning
confidence: 99%